HAS-1 genetic polymorphism in sporadic abdominal aortic aneurysm - Alberto Balbarini (Heart International, 2009)
The hyaluronan synthase 1 (HAS-1) gene encodes a plasma membrane protein that synthesizes hyaluronan (HA), an extracellular matrix molecule. Accumulating evidence emphasizes the relevance of HA metabolism in an increasing number of processes of clinical interest, including abdominal aortic aneurysm (AAA). The existence of aberrant splicing variants of the HAS-1 gene could partly explain the altered extracellular matrix architecture and influence various biological functions, resulting in progressive arterial wall failure in the development of AAA. In the present study, we assessed the hypothesis that HAS-1 genetic 833A/G polymorphism could be associated with the risk of AAA by performing a case-control association study, involving AAA patients and healthy matched donors.